Athens on the frontier : Grecian-style architecture in the splendid valley of the West, 1820-1860 - Lucas, Patrick Lee (Material Worlds Ser., 2023)
Patrick Lee Lucas examines the material culture of Grecian-style buildings in antebellum America to help recover nineteenth-century regional identities. As communities worked to define their built landscape and develop a shared Western identity, Lucas's study invites readers to question many of the assumptions Americans have made about divisions and cultural formation in antebellum society.